Changing Dynamics of the Bote Communities in Sarlahi and Tanahun: A Comparative Study - Acharya, Umesh (Rupantaran: A Multidisciplinary Journal, 2022)
The objective of this paper is to analyse the lifestyle of the Botes living in Baireni of Tanahun and Karmaiya of Sarlahi District of Nepali. Traditional livelihood patterns of both places are in transition. Now they are shifting towards agriculture, manual labour, government job, carpentry and engaging in foreign employment. To examine all these issues, this research has adopted over two geographical locations, namely Baireni of Tanahun district and Karmaiya of Sarlahi district; the method is exploratory, descriptive and comparative. In order to meet the objectives of this research, data collections were from multiple approaches. Participatory Rural Appraisal (PRA) and household surveys were two forms of the the data collection in this research. Collection of oral history, key informant interview, focus group discussion, informal meeting were also applied. It has made the entire methodology an admixture of Qual-Quan approaches. This study concludes that there are a number of instances of livelihood diversification among the Botes of Karmaiya in Sarlahi and Baireni in Tanahun district. Some of such diversifications include commercialization of farm in the rural Bote villages. This has come about because of urban expansion, expansion of various non-agricultural work opportunities in factories, workshops, private offices and to some extent government office as a result of urbanization. This supports the findings of Ellis (1998) and Babbington (1999).